PENYULUHAN KONTROL HIPERTENSI DAN DIABETES SEJAK DINI KEPADA JEMAAT GEREJA HKBP GEDUNG JOHOR RESORT, KECAMATAN MEDAN JOHOR - Anto, Endy Juli; Hutasoit, Eka Samuel P.; Siahaan, Jekson M.; Rimbun, Surjadi; Manullang, Frengky S.; Tiji, Widjaya Taufik; Tambunan, Ronald Tunggul Hotmarojahan; Lim, Hadyanto; Pasaribu, Sumihar Maurist Rantos; Tarigan, Menang Bastanta; Jamnasi, Juli; Sinatra, Jadeny; Silitonga, Hendrika Adriana (Universitas Methodist Indonesia, 2023)
Community Service (PKM) in the form of health education conducted by lecturers at the Faculty of Medicine, Indonesian Methodist University provides outreach about the benefits of controlling hypertension and diabetes mellitus from an early age. PKM was held on August 5 2023 at the HKBP church, Medan Johor District, North Sumatra. Lectures, question and answer discussions and motivation are used as orientation methods. A question and answer discussion was held with the aim of gaining insight and understanding to avoid complications from hypertension and DM. The results of PKM's socialization and work are very effective considering that there are still many people who have not received information about the benefits of vaccination through the basic immunization program. This education makes people more aware of the importance of routine control of health services. The HKBP church community must be aware and know the importance of early control in avoiding complications.